2020
DOI: 10.1093/eurpub/ckaa161
|View full text |Cite
|
Sign up to set email alerts
|

Space–time clustering and temporal trends of hospitalizations due to pulmonary tuberculosis: potential strategy for assessing health care policies

Abstract: Background Tuberculosis (TB) causes pressure on healthcare resources, especially in terms of hospital admissions, despite being considered an ambulatory care-sensitive condition for which timely and effective care in ambulatory setting could prevent the need for hospitalization. Our objectives were to describe the spatial and temporal variation in pulmonary tuberculosis (PTB) hospitalizations, identify critical geographic areas at municipality level and characterize clusters of PTB hospitaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Over the years with the evolution of technology, several studies have sought to understand the behavior of tuberculosis in space in Brazil [ 21 24 ], but few studies used temporal [ 25 , 26 ] or Spatio-temporal [ 27 , 28 ] approaches, and the numbers of studies that combined both techniques are even smaller [ 29 , 30 ]. Therefore, we encourage new studies to be carried out using spatial and temporal processes.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years with the evolution of technology, several studies have sought to understand the behavior of tuberculosis in space in Brazil [ 21 24 ], but few studies used temporal [ 25 , 26 ] or Spatio-temporal [ 27 , 28 ] approaches, and the numbers of studies that combined both techniques are even smaller [ 29 , 30 ]. Therefore, we encourage new studies to be carried out using spatial and temporal processes.…”
Section: Discussionmentioning
confidence: 99%
“…The Gini coefficient was used to select the optimal set of clusters to report when secondary spatial clusters were taken into account [ 31 ]. Following the methods outlined by Moura [ 32 ] and Santos [ 33 ], this spatial statistical analysis method involves the development of a circular window that scans the entire study. Finally, a correlation matrix plot was conducted for total and separate incidences of APOs to understand the relationship between different APOs, i.e., to what degree they were spatiotemporally similar.…”
Section: Methodsmentioning
confidence: 99%
“…[40,41] Researchers in different countries generally believe that the choice of the nursing method directly affects the rehabilitation efficiency and long-term prognosis of patients with pulmonary tuberculosis. [42][43][44] Some scholars believe that early rehabilitation nursing can promote rehabilitation of pulmonary function through timely and comprehensive rehabilitation means. [45] Greening et al [46] reported that, a series of rehabilitation training measures included in an early pulmonary rehabilitation program improved the recovery speed of patients, shortened their hospital stay, and reduced their economic burden.…”
Section: Tablementioning
confidence: 99%